2013
DOI: 10.4172/2161-0444.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Activity of Novel Series of Naphthoquinone Derivatives Attached to Benzothiophene Moiety

Abstract: A series of aryl azonaphthoquinones 8a-e were obtained via coupling of the corresponding diazonium salts 7a-c with naphthoquinones 2 or 3 in pyridine. Moreover, treatment of 5 with 6a, b in ethanol containing potassium carbonate afforded the corresponding enaminones 9a, b, respectively. Furthermore, heating of 6a with 2-hydroxy-3-((piperidn-1-yl)methyl)naphthalene-1,4-dione 10 in EtOH/AcOHor sodium 3,4-dihydro-3,4-dioxonaphthalene-1-sulphonate 1 in MeOH/H 2 O afforded the corresponding enaminones 11 and 12, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…It was inferred that the structural variations bring about change in bioactivity e.g., if halogens (Cl or Br) were substituted in the aromatic ring, it sharply enhanced the antioxidant potency of the compound (Hossain et al, 2009). The radical scavenging activity of naphthoquinones has also been studied and it was found that the antioxidant potential of 2-aminothiophene compounds has increased by introducing the naphthoquinones moiety to the compounds (Gouda et al, 2013). In the present study, among four PAN derivatives tested, the nitro and bromo derivatives have shown the better radical scavenging activity as compared to the chloro derivative, however, the methyl derivative has shown no activity at all.…”
Section: Biology: Antioxidant and Hypoglycaemic Potentialmentioning
confidence: 99%
“…It was inferred that the structural variations bring about change in bioactivity e.g., if halogens (Cl or Br) were substituted in the aromatic ring, it sharply enhanced the antioxidant potency of the compound (Hossain et al, 2009). The radical scavenging activity of naphthoquinones has also been studied and it was found that the antioxidant potential of 2-aminothiophene compounds has increased by introducing the naphthoquinones moiety to the compounds (Gouda et al, 2013). In the present study, among four PAN derivatives tested, the nitro and bromo derivatives have shown the better radical scavenging activity as compared to the chloro derivative, however, the methyl derivative has shown no activity at all.…”
Section: Biology: Antioxidant and Hypoglycaemic Potentialmentioning
confidence: 99%
“…2016). Fenol (C 6 H 5 OH) atau asam karbolat, merupakan kandungan lain dari tomat, yang terdiri dari asam aromatic dan flavonoid berperan sebagai radical scavenging dengan bertindak sebagai nitrogen untuk mencegah dan memecah siklus pembentukan radikal bebas sehingga mencegah kematian sel (Gouda et al,. 2013).…”
Section: Hasil Dan Pembahasan Pengaruh Pemberian Ekstrak Tomat (unclassified
“…A great deal of attention has been paid to 2-amino-thiophenes recently, owing to improvements in their synthetic methods, stability, availability, and structural simplicity, which makes them an important moiety in pharmaceuticals [18,19]. Furthermore, antifungal [20], antibacterial [21,22], antileishmanial [23], anxiolytic [24], anti-inflammatory [25], antiplatelet [26], antioxidant [27], antiandrogenic [28], and anti-diabetes [29] actions have been revealed for thiophene and its analogues.…”
Section: Introductionmentioning
confidence: 99%